(untitled) - Vale, Peter C. J. (Boulder, Colo., 2003)
This analysis of South Africa's postapartheid security system moves beyond a realist discussion of interacting states to examine southern Africa as an integrated whole. Despite South Africa's manipulation of state structures and elites in the region for its own ends, the text argues, the suffering endured under the apartheid regime drew the region together at the popular level, and economic factors such as the use of migrant labor reinforced the process of integration. Exploring how the region is changing today-as transnational solidarity and a single regional economy remove the distinctions between national and international politics-the book explores whether South African domination can finally be overcome and considers what sort of cosmopolitan political arrangement will be appropriate for southern Africa in the new century.
Keywords: National security,South Africa,Nam Africa,An ninh quốc gia; Politics and government,Chính quyền và chính trị; South Africa,Nam Africa